(untitled) (Journal of Nepal Geological Society, 2001)
The Proterozoic Bandai basic rocks, exposed in the Kulu-Rampur window, Lesser Himalaya, Himachal Pradesh, indicate two distinct (high-Ti and low-Ti) magma types. The majority of the basalts are characterised by high TiO2 (> 2wt %), Ti/Y, Ti/Zr, TiO2/K2O, and low Rb/Sr ratios. They are enriched with high-field-strength (HFS) elements (Nb, Zr, Ti) relative to low-field-strength (LFS) incompatible elements (K, Rb). The low-Ti basalts are characterised by low TiO2 (< 2 wt%), Ti/Y and Ti/Zr, and high Rb/Sr and Rb/Ba ratios. The common factors of the Bandai basic rocks are their quartz-normative compositions and continental tholeiitic characteristics with Nb/La always less than 1. The compositional variations in the basalt types cannot simply be explained in terms of a declining extent of crustal contamination of an asthenosphere-derived melt with time, and instead it seems that the two magma types evolved from distinct parental magmas by various degrees of partial melting. Although some of the characteristics of the basalts (especially high-Ti rocks), like low Mg number ( 30) and high concentrations of some of the LFS incompatible elements point towards assimilation and fractional crystallization process, large variations in the incompatible element ratios like Ti/Y, Ti/Zr, Rb/Sr, and Nb/La provide evidence for the derivation of these rocks through variable degrees of partial melting from an enriched mantle source. Furthermore, the Bandai basic rocks, apart from field settings, are geochemically similar to other Proterozoic basic bodies like the Rampur volcanics, Mandi- Darla volcanics, Garhwal volcanics, and Bhimtal- Bhowlai volcanics of the Lesser Himalaya. This widespread Proterozoic continental tholeiitic magmatism over an area of 170,000 km2 in the Lesser Himalaya provides an evidence of plume activity in the region.